Gestational anaemia and severe acute maternal morbidity: a population‐based study. (26th August 2020) - Guignard, J.; Deneux‐Tharaux, C.; Seco, A.; Beucher, G.; Kayem, G.; Bonnet, M.‐P.; ,
Summary: Anaemia is frequently diagnosed during pregnancy. However, there are few data regarding its incidence, and the association with severe maternal morbidity remains uncertain and potentially biased in high‐resource countries. The purpose of this study was to explore the association between gestational anaemia and severe acute maternal morbidity during and after delivery. We performed a cohort‐nested case‐control analysis from the epidemiology of severe maternal mortality (EPIMOMS) prospective study conducted in six French regions (2012–2013, n = 182, 309 deliveries). There were 1669 women with severe acute maternal morbidity during or after delivery, according to a standardised definition obtained by expert consensus. The control group were randomly selected among women without severe morbidity who delivered in the same health centres (n = 3234). We studied the association between gestational anaemia and severe acute maternal morbidity during or after delivery overall, by cause, and by mode of delivery, using multivariable logistic regression and multiple imputation. Gestational anaemia was significantly more frequent in women with severe acute maternal morbidity (25.3%) than in controls (16.3%), p < 0.001, and mostly mild in both groups. After adjustment for confounders, women with gestational anaemia were at increased risk of overall severe acute maternal morbidity during and after delivery (adjusted OR (95%CI) 1.8 (1.5–2.1)). This association was also found for severe postpartum haemorrhage (adjusted OR (95%CI) 1.7 (1.5–2.0)), even after omitting the transfusion criterion (adjusted OR (95%CI) 1.9 (1.6–2.3)), and for severe acute maternal morbidity secondary to causes other than haemorrhage or pregnancy‐related hypertensive disorders (adjusted OR (95%CI) 2.7 (1.9–4.0)). These results highlight the importance of optimising the diagnosis and management of anaemia during pregnancy.